Measurement of population dynamics in stimulated Raman adiabatic passage - Gearba, M. A.; Camp, H. A.; Trachy, M. L.; Veshapidze, G.; Shah, M. H.; Jang, H. U.; DePaola, B. D. (My University, 2007)
The temporal evolution of populations has been directly measured for a three-level ladder system undergoing coherent excitation by stimulated Raman adiabatic passage (STIRAP). The measurement technique makes use of charge transfer as diagnostic. The method is model independent and has a temporal resolution of a few nanoseconds. The temporal evolution is measured for several values of the delay between the pump and Stokes laser pulses that are part of the STIRAP excitation scheme. The corresponding quantum Liouville equations are solved and the results of the calculations are compared with experiment.